2010
DOI: 10.24156/jikk.2010.3.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Kondisi Sosial Ekonomi dan Tingkat Kesejahteraan Keluarga: Kasus di Wilayah Pesisir Jawa Barat

Abstract: ABSTRACT. Family welfare is influenced by socio-economic factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 1 publication
0
14
0
12
Order By: Relevance
“…Regional typology, community characteristics, and poverty measurement indicators are used to determine target program. 15 Waste management is done by approaching waste service by the city government and self-support community. 16 The results of this study indicated that contamination of waste can cause infectious diseases and bring vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Regional typology, community characteristics, and poverty measurement indicators are used to determine target program. 15 Waste management is done by approaching waste service by the city government and self-support community. 16 The results of this study indicated that contamination of waste can cause infectious diseases and bring vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa penelitian sebelumnya mengkaji tentang kualitas hidup secara umum dan berdasarkan aspek sosial-ekonomi (Puspitawati, 2009;Simanjuntak, Puspitawati, & Djamaludin, 2010;Muflikhati et al, 2010;Mudey et al, 2011), kualitas hidup di negara berkembang (Khizindar, 2009), dan juga kualitas hidup lansia (Netuveli & Blane, 2008). Kualitas hidup didefinisikan sebagai seberapa jauh rasa kebahagiaan atau kesejahteraan dan kepuasan yang dialami (Park & Shin, 2005).…”
Section: Pendahuluanunclassified
“…Oleh karena itu, keluarga yang memiliki aset lebih banyak cenderung lebih sejahtera jika dibandingkan dengan keluarga yang memiliki aset terbatas. Hal ini juga sesuai dengan hasil penelitian Muflikhati et al (2010) dan Iskandar (2007), bahwa aset berpengaruh signifikan terhadap kesejahteraan keluarga. Hasil penelitian juga mendukung temuan Moser dan Holland (1996) bahwa kemampuan masyarakat untuk mengatasi kesulitan ekonomi sebagian besar dipengaruhi oleh harta kekayaannya.…”
Section: Pembahasanunclassified